Sustainable competitive advantages of Singapore and Finland in global competition - Fernando W. M. D. J. (2008)
Competitiveness is one of the key factors in achieving the economic development in this protean, competitive landscape. Even though the competitiveness of the country depends upon the numerous criteria, most of them boil down to three main components namely education, technology and governance.